The Economic Conditions of a 3D Tourism Village in the Application of Pro-poor Tourism and Social Capital - Putri, Ike Karwinto; Sari, Nindya; Fikriyah; Hiddlestone-Mumford, Jacqueline; Illingworth, Juanita; Vieira, Thiago Almeida (Perencanaan Wilayah dan Kota FT UB, 2023)
Kesatrian Village has received global attention for successfully changing the image of the slum area into one of the must-visit tourist destinations in Malang City. The application of the Pro-Poor Tourism (PPT) concept to create Kampung Tridi saw village residents participate in tourism activities. This study examines the relationship between social capital and PPT tourism activities on poverty conditions. The analytical methods applied in this study include social network analysis (SNA) and descriptive analysis. PPT activities positively affect all aspects of people's lives. First, better community social capital is assumed to lead to better tourism management. Second, the relationship between social capital and tourism is directly proportional to the community's economic condition, in which more social capital generates better tourism activities, thereby reducing poverty in Kampung Tridi.